SPECIES COMPOSITION AND DISTRIBUTION OF SHARKS IN QUY NHON BAY AND NEIGHBORING WATERS - Quang, Vo Van; Tuan, Vo Si; Thao, Le Thi Thu; Thinh, Tran Cong; Vu, Nguyen Phi Uy; Phuong, Le Minh (Vietnam Journal of Marine Science and Technology, 2014)
Based on the collection including 52 samples collected during February 2010 - December 2011 in Quy Nhon bay and neiboughring waters, 12 species belonging to 7 genera, 6 families, 4 orders of sharks (Selachii) were identified. The ground sharks (Carcharhiformes) were most diverse with seven species recorded, followed by the mackerel sharks (Lamniformes) with 3 species. The dogfish sharks (Squaliformes) and carpet sharks (Orectolobiformes) included 1 species for each. The thresher shark Alopias vulpinus (Bonnaterre, 1788) was newly recorded for Vietnamese waters. The innitiative surveys on their distribution indicated that whale shark (Rhincodon typus), thresher shark (Alopias vulpinus), shortfin mako shark (Isurus oxyrinchus) live offshore and rarely observed nearshore. The spinner shark (Carcharhinus brevipina) and blacktip reef shark (Carcharhinus limbatus) live in the continental shelf and appear nearshore seasonally. Only juvenile of the silky shark (Carcharhinus falciformis) and scalloped hammerhead (Sphyrna lewini) were caught in nearshore waters. It was assumed that the pigeye (Carcharhinus amboinensis), spottail (Carcharhinus sorrah) and Japanese spurdog (Squalus japonicus) locate around the islands and outside the bay. The graceful shark (Carcharhinus amblyrhynchoides) distributes widely inside and outside the bay and around the neibouring islands. An individual of  the great white shark (Carcharodon carcharias) was caught in unhealthy status, it would be removed from the list of shark in Quy Nhon bay and neiboughring waters.